Clinical Profile and Outcome of Ventilated Children Admitted to Paediatrics Intensive Care Unit in a Tertiary Care Centre - Singh, Sandip Kumar; Khanal, Babita; Singh, Shivani (Journal of Nepal Paediatric Society, 2022)
Introduction: Mechanical Ventilation is an essential tool in paediatric critical care unit. Judicious use of ventilation when indicated, is essential along with very close clinical and hemodynamic monitoring, for successful outcome. As prolonged ventilation is associated with numerous adverse outcomes, we tried to find out common complications associated with invasive mechanical ventilation and its outcome. Methods: The study is an observational descriptive study conducted on mechanically ventilated children admitted to Paediatric Intensive Care Unit during 48 months period (November 2019 to October 2021). Demographic features included age, sex, reason for mechanical ventilation, duration of mechanical ventilation and any other comorbidities. Outcomes parameters included death in hospital, discharge from intensive care unit or shift to ward and left against medical advice (LAMA). Results: Among 1352 children admitted to PICU, 212 children (15.68%) required invasive mechanical ventilation. Common causes for mechanical ventilation were sepsis / MODS in 22.64% cases, followed by pulmonary (20.28%) and CNS infections 39 (18.39%). 166 (78.30%) children were extubated successfully, 24 (11.32%) children expired and 22 (10.37%) went on LAMA. Mortality rate of 14.18% was found in children, who were ventilated for > 72 hours, which was statistically significant. Conclusions: Ventilatory support is essential and lifesaving tool for critically ill children. Mortality rate was higher and statistically significant in children who were ventilated for > 72 hours.